Implementasi Layanan Payment Gateway Pada Aplikasi Klinik Hewan Peliharaan Berbasis Mobile - Cahyo, Fajar Dwi; Sancoko, Sulistyo Dwi; Diwandari, Saucha (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
The increasing public interest in pets means that pet clinics must provide maximum service. Pet Fams Animal Care is a service that operates in the pet sector. This research aims to make it easier for animal lovers to access pet clinics for the problems experienced by their pets. The method used to build this application system is waterfall. The result of this research is the creation of a service application that will be integrated with the Midtrans payment gateway with the Pet Fams Animal Care clinic application so that it can be a solution for animal lovers and business owners, as an effort to create an effective service.